2009
DOI: 10.2165/11317790-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Prophylactic/Functional Knee Bracing in Preventing Knee Ligament Injury

Abstract: It is estimated that knee injuries account for up to 60% of all sport injuries, with the anterior cruciate ligament (ACL) accounting for almost half of these knee injuries. These knee injuries can result in high healthcare costs, as an ACL injury is often associated with surgery, long and costly rehabilitation, differing degrees of impairment and potential long-term consequences such as osteoarthritis. The interest in ACL injury prevention has been extensive for the past decade. Over this period, many ACL (int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 175 publications
0
67
0
Order By: Relevance
“…They arrive to similar conclusions: there are some data suggesting that bracing may be effective preventing and reducing severity of MCL injuries, but there is no conclusive evidence for PKB decreasing the rate or severity of ACL injuries in football players (1,33,34).…”
Section: Clinical Studiesmentioning
confidence: 84%
See 1 more Smart Citation
“…They arrive to similar conclusions: there are some data suggesting that bracing may be effective preventing and reducing severity of MCL injuries, but there is no conclusive evidence for PKB decreasing the rate or severity of ACL injuries in football players (1,33,34).…”
Section: Clinical Studiesmentioning
confidence: 84%
“…The knee is one of the most frequently injured joints in sports, accounting for up to 60% depending on the evaluated sport, with the anterior cruciate ligament (ACL) representing almost half of these injuries (1). This is no different for skiers, where recent epidemiological reports show 84 injuries per 100,000 skiers per year (2), with knee injuries accounting for 30-38% of total injuries (2,3).…”
Section: Contextmentioning
confidence: 99%
“…The prophylactic use of knee braces in sports to prevent knee ligament injury remains controversial. Rishiraj and colleagues 14 have suggested that this inconsistency in the literature may be related in part to a fear of performance hindrance that has led to poor knee-brace compliance. Conversely, neuromuscular preventative programs have been shown to reduce the incidence of non-contact knee injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Research is limited on the use of knee braces (prophylactic and functional) to potentially prevent knee ligament injury in the non-injured population [27]. Knee braces have not to date proven to be effective in reducing the number and severity of knee injuries [19,26].…”
Section: Discussionmentioning
confidence: 99%